Can gel concentration gradients improve two‐dimensional DNA displays?. Issue 5 (31st January 2014) - Sean, David; Wang, Yixuan E.; Slater, Gary W.; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> The abrupt reduction in gel electrophoretic mobility that is observed when a dsDNA fragment is partially denatured has recently been predicted to exhibit a dependence upon the gel pore size. Using theoretical modeling, we demonstrate that this dependence can be exploited and used to improve the performance of 2D display of DNA. We report experimental evidence of this dependence and propose a new separation system in which a gel porosity gradient is utilized in a way analogous to temperature or denaturant gradients in traditional 2D display. Such gel porosity gradients can also be used in conjunction with denaturant gradients to improve 2D display results. We test these new ideas by modeling the fragment mobilities and computing the final fragment positions to find optimal 2D separation conditions.